Determinant of the quality of the national financial audit report: study at National Auditor Board Jambi Province - Yudi Yudi; Sri Rahayu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aimed to examine the effect of training, experiences, gender, age and educational background possessed by the auditor on the quality of State Financial Audit results. This research used secondary data provided by Audit Board of the Republic of Indonesia Representative of Jambi Province in the form of 2016 and 2017 staffing data and Audit Reports. Multiple linear regression analysis was used for the analysis method. The study results found that the quality of the state financial audit was affected by experiences. However, the study failed to find the influences of age, education, and gender on the quality of state financial audit results. It provides empirical evidence that the auditor's ability to find and reveal findings has been influenced by experiences of the auditor